[RETRACTED] Pengaruh Internet Terhadap Intensi Migrasi Internasional Kaum Muda di Perdesaan (Studi Kasus di Desa Tambakasri) (Diponegoro University, 2022)
RETRACTION TO:Prayitno, G., Nursaputra, Z. N., Subagiyo, A., & Wigayatri, M. (2021). Pengaruh Internet Terhadap Intensi Migrasi Internasional Kaum Muda di Perdesaan (Studi Kasus di Desa Tambakasri). TATALOKA, 23(2), 281-297. https://doi.org/10.14710/tataloka.23.2.281-297The article has been withdrawn at the request of the author.Reason:2019The published article was part of collaborative research from several authors, where the topic research came from the principal researcher, which was also part of his research roadmap. However, the principal researcher could not continue participating in the joint research because he was awarded a scholarship to study abroad. Afterward, the research was handled by the co-author.2020The research has been completed, and then compiles an article submitted to the Tataloka. The authors' composition of the articles sent to Tataloka did not mention the previous principal researcher because he was not involved in the research completion process and the preparation of the articles.2021:The article was published in Tataloka Vol. 23. No. May 2, 2021. In July, the previous principal researcher confirmed an objection to the published article. It was because the published material was part of his ongoing doctoral study. Therefore, based on COPE (Publication Ethics Committee) Retraction Guidelines, the published paper can be retracted if there are materials or data without permission to be used from the principal author.